Impaired pre-mRNA processing and altered architecture of 3' untranslated regions contribute to the development of human disorders - Michalova, Eva; Vojtesek, Borivoj; Hrstka, Roman (International journal of molecular sciences, 2013)
The biological fate of each mRNA and consequently, the protein to be synthesised, is highly dependent on the nature of the 3' untranslated region. Despite its non-coding character, the 3' UTR may affect the final mRNA stability, the localisation, the export from the nucleus and the translation efficiency. The conserved regulatory sequences within 3' UTRs and the specific elements binding to them enable gene expression control at the posttranscriptional level and all these processes reflect the actual state of the cell including proliferation, differentiation, cellular stress or tumourigenesis. Through this article, we briefly outline how the alterations in the establishment and final architecture of 3' UTRs may contribute to the development of various disorders in humans.
Keywords: Dementia; Chorea; kognitivní poruchy; expanze trinukleotidových repetic; Neoplasms; demence; dědičné degenerativní poruchy nervového systému; nádory; prekurzory RNA; chorea; lidé; Myotonic Dystrophy; 3' nepřekládaná oblast; Heredodegenerative Disorders, Nervous System; Nucleic Acid Conformation; 3' Untranslated Regions; myotonická dystrofie; Cognition Disorders; konformace nukleové kyseliny; RNA Precursors; Trinucleotide Repeat Expansion; Humans